2014
DOI: 10.4166/kjg.2014.63.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Causative Pathogens of Acute Cholangitis and Their Antimicrobial Susceptibility over a Period of 6 Years

Abstract: The most common causative pathogen of acute cholangitis was ESBL-producing E. coli. Prevalence of C. freundii increased over the time period. Imipenem should be reserved as an alternative for resistant pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In this study, 693 strains of pathogenic bacteria were isolated and 64.6% were Gram-negative bacteria. There were 210 strains of Escherichia coli (30.3%), 76 strains of Klebsiella pneumoniae (11.0%) and 32 strains of Enterobacter cloacae (4.6%), 35.4% were gram positive bacteria, including 87 strains of Enterococcus faecium (12.6%) and 71 strains of Enterococcus faecalis (10.2%), Similar to the pathogens reported in previous studies, they all belong to digestive tract bacteria [11,12,13]. It can prompt clinicians to use drugs empirically, In the treatment of patients with biliary tract infection, we can improve the function of digestive tract, maintain the patency of gastrointestinal tract and reduce the pressure in gastrointestinal tract., it can also reduce biliary tract infection theoretically [14,15].…”
Section: Discussionsupporting
confidence: 76%
“…In this study, 693 strains of pathogenic bacteria were isolated and 64.6% were Gram-negative bacteria. There were 210 strains of Escherichia coli (30.3%), 76 strains of Klebsiella pneumoniae (11.0%) and 32 strains of Enterobacter cloacae (4.6%), 35.4% were gram positive bacteria, including 87 strains of Enterococcus faecium (12.6%) and 71 strains of Enterococcus faecalis (10.2%), Similar to the pathogens reported in previous studies, they all belong to digestive tract bacteria [11,12,13]. It can prompt clinicians to use drugs empirically, In the treatment of patients with biliary tract infection, we can improve the function of digestive tract, maintain the patency of gastrointestinal tract and reduce the pressure in gastrointestinal tract., it can also reduce biliary tract infection theoretically [14,15].…”
Section: Discussionsupporting
confidence: 76%
“…In several studies performed throughout the world, the percentage of MDR bacteria isolated from the bile of patients with AC exceeded 20 to 30% [18], and intrinsically 3GC-resistant enterococci are isolated in 36–74% of AC episodes [8,28,22], particularly those involving patients with underlying biliary disease, e.g., sclerosing cholangitis [8], or a liver transplant [28]. In our study, empiric treatment with 3GC did not cover the isolated pathogens in more than 50% of patients and required the escalation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because microbes and resistance patterns show both regional and temporal variations [18,11,19], the aims of this retrospective study were to (i) characterize the contemporary microbial patterns of BD cultures performed in two German tertiary care centers using a pathogen-based approach and (ii) identify risk factors for AC by pathogens resistant to empiric antibiotic therapies and the associated outcomes using a patient-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study in patients with acute cholecystitis involving 116 institutions worldwide showed that among 96 isolated E. coli , 16 (16.7%) were producing ESBL . However, the proportion of ESBL producing E. coli varies widely region to region: 31.2% in two German university hospitals , 70.0% in Korean university medical center and 66% in Indian medical college hospital . There are few reports about the prevalence of carbapenem resistant bacteria specifically among patients with acute cholangitis and cholecystitis.…”
Section: Introductionmentioning
confidence: 99%